Pengaruh Pasta Gigi Ekstrak Strawberry(Fragaria X Ananassa Duch) Terhadap Hambatan Pertumbuhan Streptococcus MutansSecara In Vitro - Asmawati, Erni, drg.Mahmud Kholifa, MDSc, drg. Retno Sari (2016)
Caries is damage which happen on hard tissue of tooth which start from email to dentin and continuous to pulp and also have multi factorial etiology which is interaction between host, microorganism, substrate, and time. Microorganism which have role as cause of tooth caries is streptococcus mutans. Streptococcus mutans is positive gram bacteria which can release the toxin, damage cell of host dan aerobic. Prevention of caries can be done by brushing the teeth used tooth paste which contain antibacterial material. Antibacterial effect on tooth paste can be improved by herbal material such as strawberry extract in tooth paste (fragaria x ananassa duch) to barrier the growth of streptococcus mutans. The aimed of this research was understanding the effect of strawberry extract on tooth paste (fragaria x ananassa duch) to barrier the growth of streptococcus mutans and understanding of consentration of tooth paste of strawberry extract which have the biggest barrier the growth of streptococcus mutans. This research used true experimental laboratory with post test only control group design. This research used diffusion method with cakram disk which consist of 6 action group, which is tooth paste of strawberry extract with consentration 12,5%, 25%, 50%, 100%, positive control, and negative control. Barrier zone which have the shape around the holl of cakram disk analyzed using sliding caliper with millimeter. The result of this research was have antibacterial inhibition with consentration 12,5% % (d= 18,30 mm), 25% (d= 19,28 mm), 50% (d= 20,44 mm) and 100%(d= 21,47 mm). The result of One Way Anova test showed score p=0,000 (p˂0,05). The conclusion tooth paste of strawberry extract proved can inhibit the growth of Streptococcus mutans by in vitro.